2023
DOI: 10.1080/15548627.2023.2235851
|View full text |Cite
|
Sign up to set email alerts
|

LIRcentral: a manually curated online database of experimentally validated functional LIR motifs

Agathangelos Chatzichristofi,
Vasileios Sagris,
Aristos Pallaris
et al.

Abstract: Several selective macroautophagy receptor and adaptor proteins bind members of the Atg8 (autophagy related 8) family using short linear motifs (SLiMs), most often referred to as Atg8-family interacting motifs (AIMs) or LC3-interacting regions (LIRs). AIM/LIR motifs have been extensively studied during the last fifteen years, since they can uncover the underlying biological mechanisms and possible substrates for this key catabolic process of eukaryotic cells. Prompted by the fact that experimental information r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…cerevisiae and A . thaliana ) featured on LIRcentral [ 61 ], we found that this strict definition still recovers 48% of all known functional LIR motifs (and all core autophagy apparatus motifs), while rejecting 78% of non-functional ones ( S20 Table ). However, even with these restrictions, the number of motif hits in Leishmania proteomes were still very large.…”
Section: Resultsmentioning
confidence: 98%
“…cerevisiae and A . thaliana ) featured on LIRcentral [ 61 ], we found that this strict definition still recovers 48% of all known functional LIR motifs (and all core autophagy apparatus motifs), while rejecting 78% of non-functional ones ( S20 Table ). However, even with these restrictions, the number of motif hits in Leishmania proteomes were still very large.…”
Section: Resultsmentioning
confidence: 98%
“…Sequences were obtained from Uniprot and the LIR-central database (Chatzichristofi et al ., 2023). AF2-multimer was used with MMseqs2 through Google Colab ( htps://colab.…”
Section: Methodsmentioning
confidence: 99%
“…Peptides arrays were printed by the MIT Biopolymers & Proteomics Core. LIR sequences were drawn from the LIR-Central database (Chatzichristofi et al ., 2023) ( Supplemental Table 1 ). FIR sequences were drawn from (Fujita et al ., 2013; Smith et al ., 2018; Ravenhill et al ., 2019; Fu et al ., 2021; Zhou et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations